The hepatitis D satellite virus of hepatitis B virus: half-opening a new era to control viral infection?. Issue 6 (December 2016) - Abeywickrama-Samarakoon, Natali; Cortay, Jean-Claude; Dény, Paul
Abstract : Purpose of review: To highlight new concepts and therapeutic approaches concerning hepatitis D virus (HDV) infection. Recent findings: Common receptor for hepatitis B virus (HBV) and HDV has been elucidated, deciphering of HDV replication is still in progress, preliminary results of phase II proof-of-concept clinical assays for entry inhibitors and cellular farnesyl transferase inhibitors are now available. Summary: Hepatitis D infection remains a severe acute and chronic liver illness with the only currently approved therapy (Peg-αIFN) achieving disappointingly low rates of sustained viral response and clinical improvement. Both sodium taurocolate cotransporting polypeptide and heparan sulphate glypican 5 are important for viral adsorption. Preliminary results of 6 months treatment with a subcutaneous HBV PreS1-derived myristoyled peptide as an entry inhibitor indicates an encouraging short-term response with low side-effects. In addition, the short-term use of oral farnesyl transferase inhibitors induces a log10 reduction of viral RNA in almost all treated patients, but is associated with gastrointestinal upset and weight loss (especially using 200 mg/day). Encouraging results are being reported using intravenous phosphorothioate nucleic acid polymers both in terms of HBV surface antigens (HBsAg) and HDV-RNA decline; interestingly, in some patients with a strong HBsAg decline, the appearance of anti-hepatitis Bs antibodies might suggest clinical end-point improvement.